DIRECTIONAL PROPERTIES OF A CIRCULAR CYLINDRICAL PIEZOCERAMIC TRANSDUCER WITH A FLAT SCREEN IN THE DIAMETRICAL - ШИШКОВА, К. А.; КОЗАК, А. В. (Technologies and Engineering, 2023)
Purpose. The primary objective of this study is to comprehensively investigate the directional properties of a circular cylindrical piezoceramic transducer equipped with a flat screen in its diametrical plane. The research aims to assess the feasibility of enhancing the transducer's radiating characteristics through the implementation of this novel design. Methodology. The methodology employed in this research involved the utilization of the coupled field method in composite regions to determine analytical relationships for the acoustic fields generated by the screened transducer. This approach allowed for the derivation of normalized expressions for the radiation pattern and impedance. Extensive calculations and quantitative analyses were conducted to evaluate the efficacy of integrating a flat acoustically soft screen into cylindrical transducers. This assessment focused on improving their radiation properties. Findings. The study revealed several significant findings. Firstly, the placement of a flat acoustically soft screen in the diametrical plane of the transducer resulted in uniform radiation across a broad spatial angle sector and minimized sound radiation in specific directions. This innovation enabled the creation of a larger radiating surface for the transducer and facilitated unidirectional radiation. Moreover, the screened transducer demonstrated minimal alterations in radiation impedance when compared to its unshielded counterpart, simplifying the matching process with electronic generators. The research also examined the relationship between the screen's wavelength and key parameters, such as the size of the main radiation sector, the nonuniformity of the radiation pattern within this sector, and the level of backlobe radiation. It was observed that increasing the screen's wavelength led to stabilization in the values of these parameters and a reduction in backlobe radiation. This highlighted the substantial influence of diffraction processes, particularly when the screen size approached the wavelength. Furthermore, the introduction of an acoustic screen in the form of a thin flat plate in the transducer's diametrical plane significantly enhanced the acoustic loading of the cylindrical radiating shell, nearly matching that of an unshielded shell. Frequency dependencies of the radiation impedance components further emphasized the screen's minimal impact on the transducer's radiation impedance. Originality. This research introduces an innovative design for cylindrical transducers by incorporating a flat acoustically soft screen, leading to improved radiation characteristics. The analysis of diffraction processes and their impact on key parameters contributes to the originality of the study. Additionally, the research emphasizes the importance of screen size and its influence on transducer performance. Practical Value. The practical significance of this study lies in its potential to enhance the radiating properties of cylindrical transducers, making them more efficient for applications where directional radiation is crucial. This innovation has relevance in diverse fields such as sonar technology, medical ultrasound devices, defense equipment, and various other applications where optimizing acoustic characteristics is essential. Additionally, the simplified matching process with electronic generators facilitates practical implementation in real-world systems.